Introduction to biopolymers and biotech admixtures for eco-efficient construction materials - Pacheco-Torgal, F. (2016)
This chapter introduces important problems related to crude oil, the main feedstock of most polymer-based materials. These problems include interstate wars and environmental disasters. The latter is the most worrisome, such as the recent Deep Water Horizon oil spill that released approximately 780Â million liters of crude oil on the Gulf of Mexico. Some historical examples on the use of bio-admixtures in construction materials are presented. The importance of biopolymers and biotech admixtures for eco-efficient construction materials is summarized. A brief review on the role of promising biotech-based materials, like cellulose nanocrystals for eco-efficient construction, is given. An outline of the book is also given.